The Influence of Transformational Leadership Style and Employee Behavior on the Implementation of Role-Based Matrix Task Distribution in the Deputy for Investment Planning, Ministry of Investment and Downstream Industry/BKPM - Yulianti, Eka; Supriyatno, Budi; Hakim, ⁠Azis (Dinasti International Journal of Management Science, 2025)
To determine the optimality of implementing a Result-Oriented Role Matrix (RORM) task allocation in achieving an organization's vision and mission, transformational leadership style and employee behavior are essential for the effectiveness of such implementation. A transformational leader, with the ability to provide inspiration, motivation, and intellectual stimulation, can create a conducive work environment for a matrix system that demands high collaboration and accountability. Aspects of employee behavior, such as initiative, adaptability, and commitment to team goals, are also examined as supporting factors in implementing RORM-based task allocation in a measurable manner. The RORM concept is an approach in a matrix format that allocates tasks based on specific roles and maps responsibilities to avoid overlap. This research employs a quantitative approach with a causal-associative method. This approach was chosen to test the cause-and-effect relationship between independent and dependent variables. The research design is explanatory, aiming to explain the extent to which Transformational Leadership Style and Employee Behavior influence the success of the Implementation of Role-Based Output Matrix Task Division. The results indicate that transformational leadership and positive employee behavior significantly support the effectiveness of task division within a matrix structure, particularly in enhancing coordination and achieving investment objectives. This study affirms the importance of developing inspirational leadership and proactive employee behavior to optimize organizational performance within a matrix context. The practical implication is the necessity for leadership training and the enhancement of a collaborative work culture to support the implementation of matrix structures in government agency environments.